Profitability Analysis for Biomethane: A Strategic Role in the Italian Transport Sector - Cucchiella, Federica; D’Adamo, Idiano; Gastaldi, Massimo (International Journal of Energy Economics and Policy, 2015)
Biomethane is an interesting source for sustainable energy systems, featuring great flexibility that translates into multiple possible applications (vehicle fuel, combined production of thermal and electrical energy, injection in the gas grid). Compared to biogas, biomethane permits greater efficiency. Its use is not limited to the immediate area of the plant and purification of the raw methane means greater lifespans for the equipment. This paper analyses its use in the transport sector in light of recent statutory changes that introduce incentives. Net Present Value (NPV) and Discounted Payback Time (DPBT) are applied for the evaluation of profitability of biomethane plants, and are calculated in function of the feedstocks used, the plant dimensions and the firm configuration (producer and distributor combined; separate firms). Environmental considerations and a high number of natural gas vehicles (NGVs) define its strategic role in the Italian transport sector. Keywords: biomethane; economic development; sustainability JEL Classifications: 018; Q2